A new case of 8q22.1 microdeletion restricts the critical region for Nablus mask‐like facial syndrome1. Issue 1 (13th December 2012) - Debost‐Legrand, Anne; Eymard‐Pierre, Eleonore; Pebrel‐Richard, Céline; Gouas, Laetitia; Goumy, Carole; Giollant, Michel; Ayed, Wiem; Tchirkov, Andreï; Francannet, Christine; Vago, Philippe
Abstract Microdeletions of 8q21.3–8q22.1 have been identified in all patients with Nablus mask‐like facial syndrome (NMLFS). A recent report of a patient without this specific phenotype presented a 1.6 Mb deletion in this region that partially overlapped with previously reported 8q21.3 microdeletions, thus restricting critical region for this syndrome. We report on another case of an 8q21.3 deletion revealed by array comparative genome hybridization (aCGH) in a 4‐year‐old child with global developmental delay, autism, microcephaly, but without Nablus phenotype. The size of the interstitial deletion was estimated to span 5.2 Mb. By combining the data from previous reports on 8q21.3–8q22.1 deletions and our case, we were able to narrow the critical region of Nablus syndrome to 0.5 Mb. The deleted region includes FAM92A1, which seems to be a potential candidate gene in NMLFS. © 2012 Wiley Periodicals, Inc.